Studies on citric acid production by Aspergillus niger in batch fermentation - P, Pandey; S, Putatunda; L, Dewangan; S, Pawar V; A, Belorkar S (Recent Research in Science and Technology, 2013)
Citric acid is one of the very important commercial product with constant demand in the market . Citric acid production by fungi have been reported by many workers since 1913.The present study focused on production of citric acid by Aspergillus niger in batch fermentation. The maximum yield was found to be 1.5mg/ml.